Comparing STEM Majors by Examining the Relationship Between Student Perceptions of Campus Climate and Classroom Engagement. (January 2022) - Victorino, Christine; Denson, Nida; Ing, Marsha; Nylund-Gibson, Karen
This study built upon research examining the effects of diversity in STEM (science, technology, engineering, and mathematics) fields and higher education by investigating the relationship between student perceptions of campus diversity and classroom engagement for first- and second-year Latinx and White students at two structurally diverse institutions. Findings suggested that perceptions of campus climate have a positive and significant relationship with classroom engagement—which is an important indicator of overall grade point average.